Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T00:27:53+01:00
Rozwiąż równanie:
12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12-2(x²-2x+1)=4x-8-(2x²-5x-6x+15)
12-2x²+4x-2=4x-8-2x²+11x-15
10+4x=15x-23
4x-15x=-23-10
-11x=-33 /:(-11)
x=3
2010-01-12T00:28:40+01:00
12-2(x^2 +1-2x)=4x-8-(2x^2 -5x-6x+15)
12-2x^2 -2 +4x= 4x-8-(2x^2 -11x+15)
10-2x^2 +4x= 4x-8-2x^2 +11x-15 ( -2x^2 oraz 4x się skracają)
10=-8+11x-15
33=11x
x=3.
2010-01-12T00:32:25+01:00
Rozwiąż równanie:
12-2(x-1)²=4(x-2)-(x-3)(2x-5)
12 -2(x² - 2x +1) = 4x -8 - (2x² -5x -6x +15)
12 -2x² + 4x -2 = 4x -8 -2x² + 11x -15
-2x² + 4x -10 = -2x² +15x - 23
-2x² + 4x - 15x + 2x² = - 23 -10
-11x = -33
x = (-33) : (-11)
x = 33/11
x = 3